Isolation and characterization of N-fixing and IAA producing rhizobacteria from two rice field agro-ecosystems in South Sulawesi, Indonesia - Nining Haerani; ELKAWAKIB SYAM’UN; BURHANUDDIN RASYID; FERANITA HARING (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Haerani N, Syam’un E, Rasyid B, Feranita. 2021. Isolation and characterization of N-fixing and IAA producing rhizobacteria from two rice field agro-ecosystems in South Sulawesi, Indonesia. Biodiversitas 22: 2497-2503. Nitrogen-fixing bacteria that live in the rhizosphere are microorganisms that can increase N availability for rice plants in a non-symbiotic manner. Nitrogen-fixing bacteria also support growth through the production of growth hormones. These abilities are mainly influenced by the environment and their association with plants. This research aims to determine the microbial characteristics from two different rice fields agro-ecosystems (rainfed and irrigated) in South Sulawesi. Bacteria isolated from the rhizosphere soil of rice in six districts were cultured and isolated using Burk's N-free media for screening purposes. A total of 20 isolates were observed for their morphological and biochemical properties, determined their ability to fix nitrogen and produce IAA. The results showed that all isolates could grow on nitrogen-free media, in which 13 isolates were isolated from rainfed rice fields, and 7 isolates were from irrigated rice fields with various physical and biochemical properties, all other qualities tested also varied. NG4 isolate from Gowa Regency (rainfed rice field) produced the highest nitrogen (0.157%), and NB13 isolate from Barru (rainfed rice field) had the highest concentration of growth hormone (IAA) (1,835 mg L-1). All isolates obtained from rainfed rice fields showed a better ability to fix nitrogen and produce growth hormone than those from irrigated rice fields. Bacteria isolates from rainfed rice fields have higher biofertilizers and biostimulant capacity to develop environmentally-friendly rice cultivation.